IMPROVING THE METHODOLOGY FOR ASSESSING THE LEVEL OF PHYSICAL FITNESS OF SCHOOL STUDENTS ACCORDING TO AGE CHARACTERISTICS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes modern approaches to assessing the level of physical fitness of general secondary school students with due consideration of their age-related characteristics. Shortcomings of the existing assessment system are identified, and scientifically grounded methodological proposals are put forward. The improved approach highlights opportunities to ensure students’ healthy development and to enhance the effectiveness of physical education classes.